2020
DOI: 10.3846/btp.2020.11945
|View full text |Cite
|
Sign up to set email alerts
|

Social Protection and Employment in Africa’s Agricultural Sector

Abstract: Social protection is increasingly becoming a powerful tool for enhancing productivity and employment and is, therefore, important for Africa’s agricultural transformation. Thus, this study aims at examining how Africa’s agricultural sector can be transformed through social protection policies and programmes for employment. It applies the Feasible Generalised Least Squares (FGLS) econometric method on a panel of 38 African countries with the data sourced from the Country Policy and Institutional Assessment (CPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The article studies the migration phenomenon and its linkages on fiscal revenues and budget expenditures with social benefits (Cristea et al, 2019;Levchenko et al, 2017;Didenko et al, 2020b). The research (Osabohien et al, 2020;Rajan, 2018;Shammi et al, 2020) showed that social protection positively affects employers' health and work outcomes through various channels, namely, building human resources and equity, the use of public resources, social inclusion. In their study, authors (Sasongko et al, 2019; implemented the Granger Causality test and Vector Autoregression to define the causality between inflation and unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The article studies the migration phenomenon and its linkages on fiscal revenues and budget expenditures with social benefits (Cristea et al, 2019;Levchenko et al, 2017;Didenko et al, 2020b). The research (Osabohien et al, 2020;Rajan, 2018;Shammi et al, 2020) showed that social protection positively affects employers' health and work outcomes through various channels, namely, building human resources and equity, the use of public resources, social inclusion. In their study, authors (Sasongko et al, 2019; implemented the Granger Causality test and Vector Autoregression to define the causality between inflation and unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social protection can contribute to poverty reduction, empower marginalised people and be socially transformative (Devereux & Sabates-Wheeler, 2004). Social protection mechanisms such as social insurance and labour market measures allow workers to make investments and upgrade their skills because they have confidence derived from secure income and employment that eventually increases their productivity (Estevez-Abe, Iversen, & Soskice, 2001; Osabohien et al, 2020). In the wake of the COVID-19 pandemic, governments can use existing social protection programmes to identify and assist vulnerable groups who are otherwise harder to reach (Gerard, Imbert, & Orkin, 2020).…”
Section: Formal and Informal Social Protectionmentioning
confidence: 99%
“…Food security simply means a situation where all people, at all times, have physical, social and economic access to sufficient, safe, and nutritious food that meets their dietary needs and food preferences for active and healthy life [9]. Food security goes beyond availability; it includes the ability to possess monetary and non-monetary resources by the population to gain access to adequate quantities and qualities of food [10], [11]. One of the major ways to ensure food security is to engage in agriculture, this will help sustain and increase agricultural production that will feed the teeming population [12].…”
Section: Introductionmentioning
confidence: 99%